On the differences in the granular architecture and starch structure between pericarp and endosperm wheat starches. Issue 9 (8th February 2013) - Kalinga, Danusha N.; Waduge, Renuka; Liu, Qiang; Yada, Rickey Y.; Bertoft, Eric; Seetharaman, Koushik
Abstract In this study, the granular organization and structure of transitory starch from wheat pericarp was analyzed and compared to the storage starch from endosperm. Pericarp starch (PS) granules were small and spherical with fuzzy blocklets on the surface. Both starches possessed A‐type crystallinity, but the relative crystallinity and the stability of crystals were higher in PS. Iodine absorption was low in PS, but iodine slightly increased the crystallinity. PS had 14% AAM compared to 33% in endosperm starch (ES). Interestingly, the AAM (fraction II) in PS was branched as judged from the λmax value of the iodine complex, whereas ES contained linear and branched amylose. The amylopectin component (fraction I) in PS and ES mainly showed differences in the internal structure. PS amylopectin had longer chains and fewer A‐chains resulting in a less branched structure compared to ES amylopectin.